Ontogeny of the chondrocranium of the chameleon, Microsaura pumila pumila (Daudin) - Visser, J. G. J.(Jasper Gerhardus Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1965.